Costa Rica : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
This article is an analytical report of the economic developments of Costa Rica. The economy showed rapid growth in the aftermath of the global crisis with low inflation; but for further stable growth, certain policy frameworks and reforms need to be reinforced. The fiscal stance should be made tighter to mitigate risks of inflation and external imbalances. Interest rates and exchange rates must be increased, and monetary policy should be tightened for price stability. The Executive Board welcomes these measures for structural potential growth.